2023
DOI: 10.3390/insects14020116
|View full text |Cite
|
Sign up to set email alerts
|

Insecticides for Mosquito Control: Improving and Validating Methods to Strengthen the Evidence Base

Abstract: Efforts to eliminate vector-borne diseases, for example malaria which caused an estimated 619,000 deaths in 2021 [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In addition to the standard parameters such as mortality and blood feeding, sublethal exposure effect could provide complementary valuable information to better appreciate the performance of vector control strategies. It may be regarded as reductions in longevity, development rates, feeding, oviposition, fertility, fecundity, changes in sex ratio or changes in behaviour (49). Several studies have shown that insecticide resistance mechanisms can negatively affect the reproductive tness and longevity of Anopheles mosquitoes (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the standard parameters such as mortality and blood feeding, sublethal exposure effect could provide complementary valuable information to better appreciate the performance of vector control strategies. It may be regarded as reductions in longevity, development rates, feeding, oviposition, fertility, fecundity, changes in sex ratio or changes in behaviour (49). Several studies have shown that insecticide resistance mechanisms can negatively affect the reproductive tness and longevity of Anopheles mosquitoes (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Effective mosquito abatement and disease prevention strategies employ integrated approaches, and include at least seven components: (1) mosquito surveillance, in which the use of various types of traps are useful for cataloguing the vector species that are present in a geographic region; (2) physical mosquito control or source reductions focused on eliminating mosquito land and aquatic breeding sites; (3) mosquito larval control measures using chemical or biological control; (4) adult mosquito control (aduticiding) using chemical pesticides that target the stage that transmits viral and parasitic agents of human and animal disease; (5) insect resistance monitoring using cage trials and bioassays—a component that cannot be ignored as mosquitoes are extremely adaptable and can have multiple generations in a single transmission season; (6) public education on measures that can be taken to reduce or eliminate potential mosquito breeding sites, how to avoid mosquito bites, and clinical symptoms associated with vector-borne diseases; and (7) accurate record keeping to establish year-to-year trends and breeding sites, and for regulatory compliance [ 55 , 56 , 57 , 58 ]. It should be noted that synthetic repellents, such as DEET, icaridin, and permethrin, and natural oils from cedar, cinnamon, catnip, neem, and citronella, can be applied directly to skin and clothing to prevent mosquitoes from biting and foraging [ 59 , 60 , 61 , 62 , 63 ], but apart from preventing transmission when used appropriately, these personal practices have no measurable impact on the proliferation of mosquitoes in nature.…”
Section: Integrated Pest Management Programs (Ipmps) For Mosquito Con...mentioning
confidence: 99%
“…Despite the availability of a standard procedure for testing Anopheles susceptibility to chlorfenapyr, it remains vital to explore supplementary techniques that may best reflect the toxicity mechanism of the active ingredient and improve our understanding of the potential selection pressures which could drive resistance (11). Chlorfenapyr's mode of action differs remarkably from that of neurotoxic insecticides used for malaria vector control (12).…”
Section: Introductionmentioning
confidence: 99%